Investigating Secondary School Students' Difficulties in Modeling Problems PISA-Model Level 5 And 6 - Sri Imelda Edo; Ratu Ilma Indra Putri; Yusuf Hartono (Journal on Mathematics Education, 2013)
The chart of Indonesian student of mathematical ability development in Program for International Student Assessment (PISA) event during the last 4 periods shows an unstable movement. PISA aims to examine the ability of children aged 15 years in reading literacy, mathematics literacy, and science literacy. The concept of mathematical literacy is closely related to several other concepts discussed in mathematics education. The most important is mathematical modelling and its component processes. Therefore the goal of this research is to investigate secondary school students' difficulties in modeling problems PISA-model level 5 and 6. Qualitative research was used as an appropriate mean to achieve this research goal. This type of research is a greater emphasizing on holistic description, and phenomenon identified to be studied, students' difficulties in modelling real world problem in PISA model question level 5 and 6. 26 grade 9 students of SMPN 1Palembang, 26 grade 9 students of SMPK Frater Xaverius 1 Palembang, and 31 participants of mathematical literacy context event, were involved in this research. The result of investigate showed that student is difficult to; (1) formulating situations mathematically, Such as to representing a situation mathematically, recognizing mathematical structure (including regularities, relationships, and patterns) in problems, (2) evaluating the reasonableness of a mathematical solution in the context of a real-world problem. The students have no problem inÂ solve mathematical problem they have constructed.